2022
DOI: 10.3390/children9111621
|View full text |Cite
|
Sign up to set email alerts
|

Use of Virtual Reality in Children with Dyslexia

Abstract: In recent years, the study of dyslexia has seen rapid progress in definition and classification, neuropsychological correlates, neurobiological factors, and intervention. However, there are few studies on how virtual reality can affect improving cognitive domains and cross-cutting pedagogical skills. We, therefore, tested intervention through the use of a virtual reality rehabilitation system (VRRS) in children with dyslexia. Twenty-eight patients diagnosed with dyslexia were enrolled in this study. One-half u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Children with dyslexia present with deficits in higher-order processing or executive control processes. They also have peculiar eye movement tendencies [ 54 ], deficits in visual attention span, processing speed, verbal working memory [ 55 , 56 ] and difficulties with memorizing. Animal-assisted interventions represent an innovative rehabilitation approach that can improve the social, emotional and physical aspects of several diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Children with dyslexia present with deficits in higher-order processing or executive control processes. They also have peculiar eye movement tendencies [ 54 ], deficits in visual attention span, processing speed, verbal working memory [ 55 , 56 ] and difficulties with memorizing. Animal-assisted interventions represent an innovative rehabilitation approach that can improve the social, emotional and physical aspects of several diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies attribute the improvement predominantly to the simulation of reality [ 61 , 62 ]. Our research group believes that improvement is also related to the variety of stimuli selected and individualized for each child, mediation by therapists, and the experience of VR as a highly motivating playful situation [ 28 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of VRRS could be beneficial for children with DLD as it increases motivation, reduces anxiety, and causes less attractive activities to be perceived as play. These latter elements are prerequisites for more effective recovery [ 28 ]. In this field, few studies have reported the usefulness of VR in communication disorders, mainly using it to mediate caregiver–child interaction [ 29 ] or to improve communication ability in patients with autism spectrum disorder.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the application of VR in pediatric neurorehabilitation has been primarily studied in children with cerebral palsy and other types of motor impairment ( Snider et al, 2010 ; Lino et al, 2021 ; Menici et al, 2021 ; Goyal et al, 2022 ); in children or adolescents with complex outcomes due to traumatic brain injury ( Shen et al, 2020a ; Corti et al, 2022 ); and in children with neurodevelopmental disorders, such as autism spectrum disorder ( Frolli et al, 2022 ; Zhang et al, 2022 ), attention-deficit/hyperactivity disorder ( Rodrigo-Yanguas et al, 2021 ; Hong et al, 2022 ), and learning or intellectual disability ( Ahn, 2021 ; Köse et al, 2022 ; Maresca et al, 2022 ). There are limited data on the use of VR in the education and rehabilitation of children with Specific Learning Disorders (SLD).…”
Section: Introductionmentioning
confidence: 99%
“…There are limited data on the use of VR in the education and rehabilitation of children with Specific Learning Disorders (SLD). Recently, Maresca and collaborators found that a VR-based rehabilitation program had positive effects on some cognitive domains and learning abilities (word-reading and homophonic writing) in children with SLD ( Maresca et al, 2022 ). Moreover, Köse et al (2022) investigated the effects of VR on rehabilitation of visual perception skills in children with SLD and suggested that a supervised game-based intervention program is effective in improving the several subskills of visual perception.…”
Section: Introductionmentioning
confidence: 99%